Dock-Mounted, Automated, Containerized Ammunition Outloading System. - Swaney,C. B.; Franklin,R. E. (1984)
This report covers the engineering effort of Automatic Truckloading Systems Inc. (ATS) to design and detail to a Dock-Mounted Automated Containerized Ammunition Outloading System (PALS). This is a commercially manufactured system to systematically prestage and consolidate into a single load conventional ammunition, mechanically install dunnage and then rapidly outload it in 20-foot I.S.O. type 1CC containers. The system also includes three basic design goals; (1) utilization of and compatibility with existing materials handling equipment in the retail system; (2) minimum modification to the intermodal freight container; (3) system should not adversely effect unloading operations in the field. The PALS system will fit into a plan area of 100 feet by 200 feet excluding auxillary rail sidings or other modes of transport space requirements. Basic subsystems are: (A) Pals Dock Facility, (B) Dock-Mounted Loader (DML), (C) Prestaging Conveyor, (D) Overhead Traveling Crane, (E) Vehicle to Dock Interface, (F) Dunnage Handling, (G) Container Indexing (CIS), (H) Process Control, (I) Several Other Subassemblies, (I.E. Vacuum Cleaning, Dock Area Waste Material Handling & Disposal, Maintenance Support Equipment). Each of these subsystems is described in detail in this report.